مطالعہء سیرت: قرآن اور عقل کی روشنی میں (اردو کتب سیرت کے تناظر میں ) - عاصم نعیم (FIKR-O NAZAR فکر ونظر, 2012)
Muslims believe that Prophet Muhammad ﷺ is a divine Messenger for all humanity and for all times being the last in the chain of Prophethood. Thus his biography became one of the most authentic sources of Islamic teaching. Scholars of all times wrote extensively on this subject from different angles. One of these approaches is to study Sirah rationally in the light of Quran, reasoning and the authentic Prophetic traditions (Ahadith). Shibli Nuemani's Seerat-ul-Nabi has a distinct position in this context. Later Hamid-ud-din Farahi and Amin Ahsan Islahi develpoed this approach for further studies. This paper elaborates the features of this important trend in Sirah writings particularly focussing on three important biographies of the Holy Prophet ﷺ , written by Shibli Nuemani, Jafar Shah Phulwari and Khalid Masood.